Development of Networks Model in The Serious Game of Agribusiness Management for Decision Making - Bukhori, Saiful; Uta, Wiji; Andrianto, Anang (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
This research developed a decision-making process in the agribusiness management system and analyzed the behavior of fixed point for identifying the position of agribusiness interaction. Agribusiness is represented as node that work together in the market to maintain the stability of market. Based on agribusiness management and data modeling, there are four conditions of the inter-company networks: (1) mutual dependence, (2) mutual independence, (3) unbalanced dependece, (4) unbalanced independence. The experiment results are the mutual dependence conditioan the fixed point towards stable value come near 0. The mutual independence, fixed point towards stable value, but stability value still not yet come near 0. The unbalanced dependece, fixed point oscillate and convergence. While the unbalanced independence, fixed point start oscillation.